Abnormal dielectric relaxations and giant permittivity in SrTiO3 ceramic prepared by plasma activated sintering. Issue 6 (24th February 2022) - He, Zichen; Cao, Minghe; Furman, Eugene; Lanagan, Michael T.; Hao, Hua; Yao, Zhonghua; Yu, Zhiyong; Liu, Hanxing
Abstract: In this study, the dielectric properties of SrTiO3 ceramics prepared by plasma‐activated sintering (PAS) were investigated. One of the striking findings is that the material exhibits giant room temperature permittivity (k∼3.5 × 10 4 ) and low dielectric loss (∼0.05) at 1 kHz, with the permittivity exceeding that of the conventionally prepared SrTiO3 （ST） ceramics (k∼300) by two orders of magnitude. The enhancement of the polarizability was caused by the high concentration of defect dipoles. In this paper, two dielectric relaxation modes of the PAS ceramics below 0°C have been mainly discussed. One dielectric relaxation mode showed higher activation energy than that of the dielectric peak in the same temperature range for the conventional SrTiO3 ‐based ceramics. This mode was sensitive to humidity, and the strength of this mode was associated with the oxygen vacancies concentration in the ceramics. The other mode exhibited abnormal slowing down of relaxation rate with increasing temperature, which is contrary to the typical dielectric relaxation behavior, and the anomaly persisted over a narrow temperature range. Both modes were observed at the same interface between the grain and grain boundaries.